Faktor risiko anemia pada remaja putri - Andini, Widya; Apriningsih, Apriningsih; Wasir, Riswandy; Ardhiyanti, Lusyta Puri (Holistik Jurnal Kesehatan, 2026)
Background: Anaemia is a significant nutritional issue among adolescent girls, affecting growth, concentration in learning, and future reproductive health. Socioeconomic factors, dietary habits, and food quality significantly influence the prevalence of anemia.  Purpose: To determine the risk factors for anemia among adolescent girls. Method: This research was conducted at State Senior High School 1 Majalaya Karawang using an observational analytical framework. Sample comprised 230 female adolescent students, selected through purposive sampling.  Data was gathered via surveys. The investigation included the chi-square test and Cox regression to identify the primary factors affecting the prevalence of anemia. Results: The research findings indicate that factors significantly correlated with the incidence of anaemia encompass paternal education, maternal education, paternal occupation, maternal occupation, paternal income, maternal income, nutritional literacy, iron supplement consumption, nutritional status, and the quality index of nutritional intake. The primary determinant is the mother's occupation, with an odds ratio of 0.029 (p = 0.000), signifying that employed moms have a reduced chance of getting anaemia relative to their non-working counterparts. Socioeconomic and nutritional behavioral factors significantly influence the prevalence of anemia in teenage females.  Conclusion: Factors contributing to anemia in adolescent girls include father's education, mother's education, father's occupation, mother's occupation, father's income, mother's income, nutritional literacy, iron supplement consumption, nutritional status, and nutritional intake quality index. The main determinant is mother's employment status, indicated by an odds ratio of 0.029 (p = 0.000), meaning that employed mothers have a lower risk of anemia compared to unemployed mothers. These findings underscore the importance of women's economic empowerment and improving family nutritional knowledge as methods to reduce the prevalence of anemia in the community.   Keywords: Anaemia; Adolescent Girls; Nutrition Literacy; Nutritional Status; Quality of Nutrient Intake.   Pendahuluan: Anemia adalah masalah gizi yang signifikan di kalangan remaja putri, memengaruhi pertumbuhan, konsentrasi dalam belajar, dan kesehatan reproduksi di masa depan. Faktor sosial ekonomi, kebiasaan makan, dan kualitas makanan secara signifikan memengaruhi prevalensi anemia. Tujuan: Untuk mengetahui faktor risiko anemia pada remaja putri. Metode: Penelitian ini dilakukan di SMA N 1 Majalaya Karawang dengan menggunakan kerangka analitis observasional. Sampel penelitian terdiri dari 230 siswa remaja perempuan yang dipilih melalui pengambilan sampel, data dikumpulkan melalui survei. Penyelidikan ini mencakup uji chi-kuadrat dan regresi Cox untuk mengidentifikasi faktor utama yang memengaruhi prevalensi anemia. Hasil: Faktor-faktor yang berkorelasi signifikan dengan kejadian anemia meliputi pendidikan ayah, pendidikan ibu, pekerjaan ayah, pekerjaan ibu, pendapatan ayah, pendapatan ibu, literasi gizi, konsumsi suplemen zat besi, status gizi, dan indeks kualitas asupan gizi. Penentu utama adalah pekerjaan ibu, dengan rasio odds 0.029 (p = 0.000), yang menunjukkan bahwa ibu yang bekerja memiliki peluang lebih kecil untuk menderita anemia dibandingkan dengan rekan mereka yang tidak bekerja. Faktor perilaku sosial ekonomi dan gizi secara signifikan memengaruhi prevalensi anemia pada remaja putri. Simpulan: Faktor anemia pada remaja putri meliputi pendidikan ayah, pendidikan ibu, pekerjaan ayah, pekerjaan ibu, pendapatan ayah, pendapatan ibu, literasi gizi, konsumsi suplemen zat besi, status gizi, dan indeks kualitas asupan gizi. Penentu utamanya adalah status pekerjaan ibu, yang ditunjukkan oleh rasio odds sebesar 0.029 (p = 0.000), yang berarti bahwa ibu yang bekerja memiliki risiko anemia lebih rendah dibandingkan dengan ibu yang tidak bekerja. Temuan ini menggarisbawahi pentingnya pemberdayaan ekonomi perempuan dan peningkatan pengetahuan gizi keluarga sebagai metode untuk mengurangi prevalensi anemia dalam masyarakat.   Kata Kunci: Anemia; Literasi Gizi; Mutu Asupan Gizi; Remaja Putri; Status Gizi.